297 Positive shifts in knowledge, attitudes and practice after a 60-minute CPR-AED training. (1st May 2022) - White, AE; Hong, M; Poh, JS; Lum, N; Jalil, A; Kua, PHJ; Ong, MEH
Abstract : Background: Training and motivating more laypeople to respond to out-of-hospital cardiac arrest (OHCA) is associated with improved OHCA survival rates. This study involved measuring the change in knowledge, attitudes and practice after a 60-minute CPR-AED training. Method: We administered pre-/post-training surveys to 337 participants who underwent CPR/AED training. McNemar's and paired t-tests were used to analyse responses. Compression performance was measured during 2 compression performance rounds on the same day. Results: Favourable shift in knowledge was observed in post-training survey (p<0.001) as follows: 'First thing to do…' (pre 48.2% vs post 90.9%, p<0.0001); 'Correct number to dial…' (pre 88.4% vs post 99.7%, p<0.0001); '…after getting dispatcher on the phone…' (pre 65.5% vs post 96.0%, p<0.0001); '…how deep to compress' (pre 47.0% vs post 96.4%, p<0.0001); '…how fast to compress' (pre 14.7% vs post 56.1%, p<0.0001). Attitudes improved towards CPR and AED use where 71.5% and 72.5% said 'I don't know/unlikely/very unlikely' to perform CPR and use AED at pre-training then improved to 79.5% and 82.2% would 'likely/very likely' afterwards. In CPR practice, average optimal CPR compression depth improved from 70% to 74.9% (t(336)=-3.74, p<0.001); however, compressions at >120 per minute increased from 22.5% to 31.1% (t(336)=-5.72, p<0.001). Conclusion: We observed favourable shifts in knowledge, attitudes and practice for CPR-AED use amongst our participants that were likely due to undergoing the brief CPR/AED training. The increased average rate observed in the second round of compressions could be an effect of fatiguing. Conflict of interest: None. Funding: Ministry of Health, Singapore.